Periferní zlomeniny talu – střednědobé výsledky operační léčby - Peml, Marek; Kálal, P; Kopačka, Pavel; Kloub, Martin (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2016)
PURPOSE OF THE STUDY Peripheral fractures of the talus (lateral talar process and posterior talar process) are rare injuries, easy to miss on examination due to their location and clinical manifestation. They account for 0.3% to 1.0% of all fractures of the talus. An incorrect or late treatment of talar process fractures can result in permanent pain, impingement syndrome, healing in malposition, pseudoarthrosis development and also, due to joint instability, in a potential development of severe subtalar arthritis. The aim of this retrospective study was to evaluate the results of surgical management of these fractures in our department. MATERIAL AND METHODS The study included 14 adult patients with fractures of the peripheral talar processes who met the criteria of the retrospective study and were treated in our department between 2008 and 2014. All patients underwent clinical examination with evaluation based on the AOFAS Ankle-Hindfoot score, VAS score and radiographic evidence of arthritis. Follow-up ranged from 24 to 95 months. The average age of the patients at the time of surgery was 34 years (range, 21-59 years); there was one woman and 13 men. All underwent pre-operative CT scanning. The surgical procedure included open reduction and internal fixation (ORIF) which, in indicated cases, was preceded by partial or total removal of the processes. RESULTS Of the 14 patients, seven were treated for fractures of the lateral talar process (LTP group) and seven for the posterior talar process (PTP group). All fractures healed completely. The median AOFAS score was 87 (72-100) points in the LTP group, and 84 (58-100) points in the PTP group. Excellent and good results on the AOFAS Ankle-Hindfoot scale were achieved in 10 (72%), satisfactory in two (14%) and poor in two (14%) patients. Of the LTP group, six patients (86%) showed the VAS score ≤ 3, and one (14%) had the VAS score = 4. In the PTP group, the VAS score ≤ 3 was reported by three (43%) and values of up to 5 by four (57%) patients. Arthritis in the talocrural and subtalar joints was evaluated as zero or grade 1 in 11 (79%) of all patients; of these 11 patients only two (14%) had a VAS score higher than 3. Only one patient had marginal wound necrosis; no deep wound infection was recorded. DISCUSSION The majority of fractures in our group were due to falls from a height or traffic accidents, which is in accordance with the literature data. In about 70% of these injuries, more parts of the leg are affected and, therefore, a thorough medical inspection is necessary. These mechanisms of injury most frequently produce type II LTP fracture (Hawkins classification). Four patients with a LTP fracture, who had the process partially removed, achieved good results on the AOFAS scale and the VAS score less than or equal to 3. As also published in the literature, the removal of small fragments has no crucial effect on ankle stability. CONSLUSIONS An adequate surgical treatment of displaced peripheral fractures of the talar processes provides good functional outcomes. In fractures with associated leg injuries or high-energy traumata, the prognosis is poorer. Fractures of talar processes often show symptoms and signs similar to those of more serious forms of dislocation of the talus and therefore a careful assessment of standard X-ray images taken for a "swollen ankle" is necessary. If the findings are not clear, CT examination is indicated. Key words: fracture, talus, processus lateralis tali, processus posterior tali.
Keywords: spokojenost pacientů; dospělí; fraktury kostí; Female; Adult; Patient Satisfaction; výsledek terapie; ženské pohlaví; mladý dospělý; Tomography, X-Ray Computed; Accidents, Traffic; lidé; Fractures, Bone; Treatment Outcome; Talus; Humans; retrospektivní studie; Male; Young Adult; Accidental Falls; vnitřní fixace fraktury; lidé středního věku; talus; mužské pohlaví; úrazy pádem; Retrospective Studies; Middle Aged; Fracture Fixation, Internal; dopravní nehody; počítačová rentgenová tomografie